Diminishing the side effect of mitomycin C by using pH-sensitive liposomes: in vitro characterization and in vivo pharmacokinetics - Fang YP; Hu PY; Huang YB (Dove Medical Press, 2018)
Yi-Ping Fang,1,2 Pei-Yu Hu,1 Yaw-Bin Huang1,3 1School of Pharmacy, College of Pharmacy, Kaohsiung Medical University, 2Department of Medical Research, Kaohsiung Medical University Hospital, 3Center for Stem Cell Research, Kaohsiung Medical University, Kaohsiung, Taiwan Introduction: Mitomycin C is an anticancer antibiotic agent that has the potential for broad-spectrum use against several cancers, including mammary cancers. Because its half-life is 17 min after a 30 mg intravenous bolus administration, the suitability of mitomycin C for wide use in the clinical setting is limited. Based on tumor pathophysiology, pH-sensitive liposomes could provide better tumor-targeted effects. The aim of this study was to investigate the possibility of diminishing the side effect of mitomycin C by using pH-sensitive liposomes.Materials and methods: pH-sensitive liposomes was employed to deliver mitomycin C and evaluate the characterization, release behaviors, cytotoxicity, in vivo pharmacokinetics and biochemical assay.Results: The results demonstrated that mitomycin C-loaded pH-sensitive liposomes had a particle diameter of 144.5±2.8 nm and an entrapment efficiency of 66.5%. The in vitro release study showed that the pH-sensitive liposome release percentages at pH 7.4 and pH 5.5 were approximately 47% and 93%, respectively. The cell viability of MCF-7 cells showed that both the solution and liposome group exhibited a concentration-dependent effect on cell viability. The MCF-7 cell uptake of pH-sensitive liposomes with a folate modification was higher which was indicated by an increased fluorescence intensity compared to that without a folate modification. The area under the concentration–time curve of mitomycin C-loaded pH-sensitive liposomes (18.82±0.51 µg·h/L) was significantly higher than that of the mitomycin C solution group (10.07±0.31 µg·h/L). The mean residence times of the mitomycin C-loaded and mitomycin C solution groups were 1.53±0.16 and 0.05 h, respectively. In addition, there was no significant difference in terms of Vss (p>0.05). Moreover, the half-life of pH-sensitive liposomes and the mitomycin C solution was 1.35±0.15 and 1.60±0.04 h, respectively. In terms of safety, mitomycin C-loaded pH-sensitive liposomes did not affect the platelet count and the levels of blood urea nitrogen and aspartate aminotransferase.Conclusion: The positive results of pH-sensitive liposomes demonstrated maintained the cytotoxicity and decrease the side effect. Keywords: mitomycin C, liposomes, pH-triggered release, pharmacokinetics, side effect